Blockchain Technology, Internal Control, and Company Size in Reducing Audit Report Lag in Manufacturing Companies on IDX Syariah - Shinta, Alivia Feby; Risnaeni, Umi Suswati (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study examines the influence of Blockchain Technology, Internal Control, and Company Size on Audit Report Lag (ARL) in manufacturing companies listed on the IDX Syariah for the 2021-2025 period, focusing on the potential of digital innovation and oversight mechanisms to enhance financial reporting efficiency. Utilizing a quantitative approach with multiple regression analysis, data were collected through purposive sampling from the annual reports of issuers consistently listed in the sharia index. The results indicate that, both partially and simultaneously, Blockchain Technology, Internal Control, and Company Size have no significant effect on audit report lag. The very low Adjusted R-squared value suggests that the adoption of blockchain technology and internal control structures is currently still administrative or a matter of regulatory compliance, thus failing to fundamentally transform conventional substantive audit procedures. This research provides a contribution to regulators and audit practitioners to accelerate the development of digital-based audit standards and encourage the strengthening of internal control quality so that it can provide a tangible contribution to financial reporting efficiency in the Indonesian sharia capital market.